2015
DOI: 10.1016/j.tate.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding teachers' responses to enactments of sexual and gender stigma at school

Abstract: Although teachers may be in a position to address enactments of sexual and gender stigma among their students, little is known about their motivations to intervene in such situations. We surveyed secondary school teachers in the Netherlands, assessing how beliefs, norms, and self-efficacy were related to their intentions to intervene in two hypothetical situations that involved bullying of lesbian/gay or gender non-conforming students. We found significantly stronger intentions to intervene among teachers who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 41 publications
4
30
1
3
Order By: Relevance
“…The finding that teachers with higher self‐efficacy beliefs report intervention in bullying situations more often is in line with most findings in the current literature (e.g., Bradshaw et al, ; Collier et al, , Duong & Bradshaw, ; Williford & Depaolis, ; Yoon, ). But in the present article, this result was not found for teachers' intention to intervene as assessed in hypothetical situations or typical behaviors (readiness to intervene), but rather for their intervention in situations they actually experienced (probability of intervention).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The finding that teachers with higher self‐efficacy beliefs report intervention in bullying situations more often is in line with most findings in the current literature (e.g., Bradshaw et al, ; Collier et al, , Duong & Bradshaw, ; Williford & Depaolis, ; Yoon, ). But in the present article, this result was not found for teachers' intention to intervene as assessed in hypothetical situations or typical behaviors (readiness to intervene), but rather for their intervention in situations they actually experienced (probability of intervention).…”
Section: Discussionsupporting
confidence: 90%
“…In the case of less-experienced teachers, Duong and Bradshaw (2013) found that self-efficacy was, in fact, the only relevant predictor of intervention. The connection between self-efficacy and teachers' readiness to intervene has been found in cyberbullying (Boulton, Hardcastle, Down, Fowles, & Simmonds, 2014;Williford & Depaolis, 2016) as well as traditional bullying (Collier et al, 2015;Dedousis-Wallace, Shute, Varlow, Murrihy, & Kidman, 2013).…”
Section: Bullying Intervention Self-efficacy and Teachers' Intervenmentioning
confidence: 99%
See 3 more Smart Citations